Voices of the poor : from many lands - Narayan-Parker, Deepa; Petesch, Patti L. (Washington, DC : A copublication of Oxford University Press and the World Bank, 2002)
Voices of the Poor provides a unique and detailed picture of the life of the poor and explains the constraints poor people face to escape from poverty in a way that more traditional survey techniques do not capture well. From Many Lands, the third volume in the Voices of the Poor series, contains regional findings and 23 country cases, grouped by region.
"World Bank"--Cover.
Includes bibliographical references.
rpm 21/09/16
Loans
Keywords: Poor; Poverty; Poor -- Attitudes .; Poverty -- Case studies; Social Science